Protein arginine methylation/demethylation and cancer - Poulard, Coralie (Oncotarget, 2016)
Protein arginine methylation is a common post-translational modification involved in numerous cellular processes including transcription, DNA repair, mRNA splicing and signal transduction. Currently, there are nine known members of the protein arginine methyltransferase (PRMT) family, but only one arginine demethylase has been identified, namely the Jumonji domain-containing 6 (JMJD6). Although its demethylase activity was initially challenged, its dual activity as an arginine demethylase and a lysine hydroxylase is now recognized. Interestingly, a growing number of substrates for arginine methylation and demethylation play key roles in tumorigenesis. Though alterations in the sequence of these enzymes have not been identified in cancer, their overexpression is associated with various cancers, suggesting that they could constitute targets for therapeutic strategies. In this review, we present the recent knowledge of the involvement of PRMTs and JMJD6 in tumorigenesis.